Oxidative Stress and DNA Damage in Mice Kidneys Exposed to Cadmium Chloride - Masoomi karimi, Masoomeh; Zareemahmudabadi, Ali; Jafarisani, Moslem (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background: Cadmium is one of the most toxic heavy metals in our environments having a very strong ability to accumulate in body organs especially in kidney. Our aim of this study is to determine of the genotoxicity and cytotoxicity in mice kidneys exposed to cadmium. Material and Method: In this study we sacrificed 30 male mice and randomly divided into 2 different groups (control& case). Every 5 mice remained in one cage at the same standard conditions. After a week, the mice were exposed to Cd (300µm/Kg.b.wt) on 0, 6, 12, 24, 48 hrs by peritoneal injections. After 24hrs from the latest injection, the mice were killed and obtained their kidneys, and then the oxidative stress markers (malondialdehide (MDA), glutathione (GSH) and superoxide dismutase (SOD)) were assayed on homogenized kidneys in order to study of cytotoxicity, genotoxicity and DNA damage. We used Comet assay on separated kidney cells. Finally, for analyzing statistical data, we used T-test and ANOVA using SPSS15 software. Results: In treated group, MDA and GSH concentration and also SOD (ρ<0.05) activity significantly increased in comparison with control group. Conclusion: The comet assay results obviously showed DNA breakage stimulated by Cd in treated group it was not seen in the control group.